Kualitas Asuhan Keperawatan di Era Pandemi COVID 19 Berdasarkan Perspektif Pasien Ruang Rawat Inap Anggrek di Rumah Sakit Advent Medan - Kristiani Marbun; Afnijar Wahyu (Jurnal Kesehatan Amanah, 2025)
The quality of nursing care is a care provided that meets the needs of patients, provides comfort, maintains mental, provides satisfaction, provides sincere satisfaction in a professional manner (Daniel, 2021). There are several instruments developed to assess the quality of nursing care, namely the patient's assement of quality scale-acute care version (PAQS-ACV) instrument that there are five domains used to assess the quality of care, namely 1) caring attention and concern for patients, 2) individualization prioritizes patients and supports patients with problems faced and treats patients like humans, 3) responsiveness where a nurse must be responsive to patients and must be ready to meet patient needs, 4) nurse characteristics nurses must have good character towards patients, 5) enviroment where a sense of comfort in a calm environment for patients (Mendrofa, 2021). This type of research is quantitative with a simple descriptive design using non-probality sampling technique with the Kolmogrov-Smirnov method using the Slovin formula and the number of 86 respondents. The results showed that the quality of nursing care based on the patient's perspective at the Adventist Hospital in Medan in 2021 has a good value according to the questionnaire.